1976
DOI: 10.1113/jphysiol.1976.sp011479
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of food intake in the rat following complete absorption of glucose delivered into the stomach, intestine or liver.

Abstract: SUMMARY1. Solutions of glucose or other carbohydrates were administered during the dark or light period of the circadian cycle to rats which had been only briefly deprived of food.2. Food was restored to the animals at various times after administration of a glucose load by stomach tube. With delays between loading and access to food of up to 3 hr by night and 2 hr by day, subsequent food intake was less than intake after non-nutritive loads.3. Measurement of the glucose content of the gastrointestinal tract a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…This satiating effect was observed only in free-feeding sham-operated rabbits and not in fasted sham-operated rabbits or vagotomized rabbits following fasting or continuous access to food. These data are consistent with reports that intraduodenal glucose administration reduced feeding in several species (Booth & Jarman, 1976;Heron & Stephens, 1978;Houpt, Houpt, & Pond, 1979;Novin et aI., 1974). The failure of other investigations (Ehman et aI., 1971;Glick, 1979;Yin & Tsai, 1973) to demonstrate nutrient-specific suppression of feeding after intraduodenal glucose infusion may be due to the use of long-fasted subjects, which have previously been shown to be less sensitive to the satiating effect of glucose infusion (present experiment; Novin et aI., 1974).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This satiating effect was observed only in free-feeding sham-operated rabbits and not in fasted sham-operated rabbits or vagotomized rabbits following fasting or continuous access to food. These data are consistent with reports that intraduodenal glucose administration reduced feeding in several species (Booth & Jarman, 1976;Heron & Stephens, 1978;Houpt, Houpt, & Pond, 1979;Novin et aI., 1974). The failure of other investigations (Ehman et aI., 1971;Glick, 1979;Yin & Tsai, 1973) to demonstrate nutrient-specific suppression of feeding after intraduodenal glucose infusion may be due to the use of long-fasted subjects, which have previously been shown to be less sensitive to the satiating effect of glucose infusion (present experiment; Novin et aI., 1974).…”
Section: Discussionsupporting
confidence: 82%
“…Although some investigations have failed to observe nutrient-specific satiety following glucose infusion into the alimentary tract (Ehman, Albert, & Jamieson, 1971; Glick, 1979;Yin & Tsai, 1973), the use of long-fasted animals may have been a reason for the absence of satiety, since the depression in feeding produced by intraduodenal glucose infusion in free-feeding rabbits was absent following a fast (Novin et aI., 1974). VanderWeele, Skoog, and Novin (1976) demonstrated that intraduodenal glucose administration decreased feeding in freefeeding rabbits but not in rabbits fasted for even as short a period as 2 h. The magnitude of the glucose load also plays a very important role in determining its modulatory influence on feeding, since a small duodenal infusion (3.5 mIl kg BW) of 5% glucose decreased food intake in free-feeding rabbits, where~s a larger load (10.5 mIlkg BW) of 5070 glucose actually intake to caloric availability (Booth & Jarman, 1976;Friedman & Stricker, 1976). Thus, one rationale for the present study was to determine the relation between the glucose load (produced by varying glucose concentration) and subsequent feeding.…”
mentioning
confidence: 99%
“…Recently, the intestine has been considered as a possible site of glucoreceptors (Mei, 1978). Experimental evidence for such glucoreceptors active in the short-term control of food intake in the rabbit (Novin, Sanderson & VanderWeele, 1974) and the rat (Yin & Tsai, 1973;Booth, 1972b;Booth & Jarman, 1976) has been ambiguous and has varied with the experimental procedures.…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear whether the postulated receptors are sensitive only to glucose or to other metabolites as well. Intraportal infusions of glucose have suppressed food intake in dogs (Russek, 1970), rats (Booth & Jarman, 1976), rabbits (VanderWeele et al 1976) and chickens (Shurlock & Forbes, 1981). In contrast, some studies have failed to demonstrate an effect on feeding of glucose infusion into the liver.…”
Section: Sensory Functions Of the Livermentioning
confidence: 99%